Pathways for Entry of Livestock Arboviruses into Great Britain: Assessing the Strength of Evidence. Issue 2 (12th January 2015) - Gale, P.; Kelly, L.; Snary, E. L.
Summary The emergence of bluetongue virus and Schmallenberg virus in Great Britain (GB) during the last decade has highlighted the need for understanding the relative importance of the various pathways of the entry of livestock arboviruses so as to help focus surveillance and mitigation. This study summarizes what is known for the main routes of entry and assesses the strength of the current evidence for and against. Entry through infected arthropod vectors is considered at the level of each life cycle stage for tick‐, biting midge‐ and mosquito‐borne viruses, and while there is evidence that this could happen through most tick and mosquito stages, strong evidence that only exists for entry through adult midges. There is also strong evidence that entry through immature midge stages could not happen. The weight of supporting evidence is strongest for importation of viraemic livestock including horses. While there is some indication of a common pathway for midge‐borne viruses from sub‐Saharan Africa to GB via Continental Europe, other factors such as maternal transmission in dogs and sheep need to be considered in the light of recent findings.